Migrants in the job centre: Qualitative findings on migrants' experiences with public employment support services in Germany - Jan Schneider; Michael Fischer; Vesela Kovacheva (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2008)
The inclusion of migrants into the labour market is considered a key issue in order to achieve better overall integration. However, compared to the German population, unemployment rates are around twice as high among foreigners. One important knob to improve access to the labour market lies in publicly funded counselling and services, a field which has undergone fundamental policy reforms in recent years. In order to illuminate the realities of everyday-encounters between authoritative services and unemployed migrants, to identify possible shortcomings and draw some conclusions for policy development, this paper focuses on the subjective views and experiences of migrants related to the various employment services and agencies. On the basis of a qualitative interview sample, several patterns of experiences within public employment-related agencies are identified, including the perceived role of counsellors, courses and training measures, questions of diversity, discrimination and transparency as well as the overall outcome in terms of job referral and service evaluation.
Keywords: 330